Feasibility Strategy on Giving Capital for Salt Farmers in Increasing Economic Productivity Using KNN Classification Model - Yusniar Yusniar; Umaruddin Usman; Mutammimul Ula; Fakrurrazi Fakrurrazi; Salamah Salamah; Muarif Qumar (Jurnal Mantik, 2021)
The strategy of increasing the salt business in the development of the marine (coastal) economy is very significant in boosting the productivity of the salt. The business of salt that located on Coastal has very good prospects in the future because it is supported by a lot of potential for vacant land, climate, human resources, market opportunities and abundant raw materials for the manufacture of people's salt. Socio-economic potential is the basic capital in the development of salt production in North Aceh Regency, especially Aceh Province. The current issue for most salt farmers is that the quality of salt is still low which is caused by the existing access to capital by farmers, other problems, lack of capital is one of the causes of the decline in salt productivity so that the salt produced is not in accordance with market demand.Salt farmers experienced the impact of a decrease in the productivity of business capital, which became an obstacle for the investor of capital. This can be resolved by the financier. Then the bank can provide funds to salt farmers according to their needs. Therefore, the importance of research in implementing a banking strategy in increasing the productivity of salt farmers in accordance with the business of the farmer group. It is very important to analyze the productivity of salt farmers after being given capital to assess the success of the capital provided to salt farmers. This research method begins with a survey of strategic information in providing business capital for salt farmers which is useful in increasing the productivity of salt farmers. The results of the analysis are entered into the K-Nearest Neighbor classification model in the feasibility of providing capital using a classification in order to see groups of productive salt farmers after being given capital. The results of the test with the k-means clustering model are in the form of group 2 classification values with a distance value of 0.210 based on the criteria included in the strategy for providing business capital.